Simulation of discrete control systems with parallelism of behavior - D. I. Cheremisinov; L. D. Cheremisinova (Informatika)
Objectives. The problem of functional verification of control devices with respect to their design specification is considered. When solving the problems of implementing and testing of discrete systems, one has to deal with the presence of parallelism in the behavior of interacting control objects, which is also displayed in the assignment for designing control systems. The aim of the work is to develop a method for simulating descriptions of such systems, which allows their behavior testing dynamically on the area limited by their possible functioning.Methods. The paper considers a class of control systems with parallelism of the processes occurring in them, which permits linearization of their execution. To specify the behavior of such control systems, it is proposed to use the PRALU language of parallel control algorithms, which is based on Petri nets and which allows to order events occurring during the device operation. An object-oriented approach to simulation of the description of the control algorithm at the transaction level is proposed. For this purpose, a TLM (Transaction-Level Modeling) model has been developed for describing the devices with behavior parallelism in PRALU language. The transaction level model describes a system as a set of interacting processes that run in parallel and determine the behavior of the system over time.Results. The key concepts of the TLM model for simulating the descriptions of control algorithms in the PRALU language are defined: data structure, transactions, processes, and a barrier mechanism for synchronization of parallel processes. A method is proposed for transforming the description of an algorithm in the language into a TLM model, which is based on the representation of language operations as compositions of elementary operations that are performed sequentially. The set of these operations forms the basis for the algorithmic decomposition of a parallel algorithm in PRALU language into intermediate language program that is executed strictly sequentially. Translators of this program into the Verilog and C languages have been developed, the results of their compilation are simulators of the behavior of control system.Conclusion. The proposed simulation method can be used to create a test bench for functional verification of the circuit implementation of control devices with behavior parallelism. In this case, test sequences for verifying the circuit implementation can be generated dynamically – in the process of simulating the description of the algorithm in the PRALU language directly the control device or system, which include the control algorithm and the algorithms of controlled objects behavior.